The effect of the prohibition of aviation in the income account for ticket companies: An applied study of a sample of companies and offices operating in the city of Erbil - المدرس المساعد ديار عبدالمجيد; المدرس المساعد درباز انور اسماعيل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The effect of the prohibition of aviation in the income account for ticket companies: An applied study of a sample of companies and offices operating in the city of Erbil There is no doubt because of the referendum process in the Kurdistan Region on September 25, 2017, the Iraqi government imposed a ban on aviation on September 29 on the airports of Arbil and Sulaymaniyah and continued until March 13, 2018, which negatively affected the economic activities, especially on the activities of ticket companies in the city of Arbil. Where the results indicated: 1- The ratio of (100%) of airlines companies and offices indicated the weakness of demand for their services due to the imposition of a ban on flights on the airports of the Kurdistan Region - Iraq during the period 29/9 / 2017-13 / 3/2018. 2 - The Turkish, Qatari and UAE airlines are more dominant in the air markets in Erbil. This can be attributed to several reasons, including geographical, economic and political, especially between the Kurdistan Region of Iraq and Turkey and Qatar of the UAE. 3- The proportion of (92.84%) companies and aeronautical offices in the city of Erbil the size of their daily loss due to the prohibition of aviation between (1-800) US dollars. 4 - The rate of change for the average of the total prices after the ban of aviation compared to the average total prices before the ban of aviation amounted to (32.24%). This increase is due to the ban on flights because passengers have to travel to Baghdad and then make the international flight. The research reached a number of proposals: 1. The Erbil and Sulaymaniyah airports administrations are required to study the calculation of their losses during the air embargo period, based on researchers and specialists in this field, in order to claim compensation from the Iraqi government. 2. Establishing a specialized association for owners of airlines and airlines in the Kurdistan Region, in order to defend their legitimate rights in this field. 3.Owners of companies and offices of aviation in the Kurdistan Region claim compensation for their loss during that period of the provincial government and the federal government.